Beyond FOXP3: a 20-year journey unravelling human regulatory T-cell heterogeneity - Santosh Nirmala, Samikshya; Kayani, Kayani; Gliwiński, Mateusz; Hu, Yueyuan; Iwaszkiewicz-Grześ, Dorota; Piotrowska-Mieczkowska, Magdalena; Sakowska, Justyna; Tomaszewicz, Martyna; Marín Morales, José Manuel; Lakshmi, Kavitha; Marek-Trzonkowska, Natalia Maria; Trzonkowski, Piotr; et al. (Frontiers in Immunology, 2024)
The initial idea of a distinct group of T-cells responsible for suppressing immune responses was first postulated half a century ago. However, it is only in the last three decades that we have identified what we now term regulatory T-cells (Tregs), and subsequently elucidated and crystallized our understanding of them. Human Tregs have emerged as essential to immune tolerance and the prevention of autoimmune diseases and are typically contemporaneously characterized by their CD3+CD4+CD25high CD127lowFOXP3+ phenotype. It is important to note that FOXP3+ Tregs exhibit substantial diversity in their origin, phenotypic characteristics, and function. Identifying reliable markers is crucial to the accurate identification, quantification, and assessment of Tregs in health and disease, as well as the enrichment and expansion of viable cells for adoptive cell therapy. In our comprehensive review, we address the contributions of various markers identified in the last two decades since the master transcriptional factor FOXP3 was identified in establishing and enriching purity, lineage stability, tissue homing and suppressive proficiency in CD4+ Tregs. Additionally, our review delves into recent breakthroughs in innovative Treg-based therapies, underscoring the significance of distinct markers in their therapeutic utilization. Understanding Treg subsets holds the key to effectively harnessing human Tregs for immunotherapeutic approaches.